Diameter increment and periodicity of growth rings of two tree species in a tropical rainforest of northern Oaxaca, Mexico - Pineda-Herrera, Elizandro; Valdez-Hernández, Juan Ignacio; López-López, Miguel Ángel; Filemón, Filemón; Salgado-Ugarte, Isaías Hazarmabeth (Instituto de Ecología, A.C., 2016)
Diameter growth was estimated and periodicity of the growth rings was determinated for Schizolobium parahyba and Vochysia guatemalensis in a tropical rain forest of Comaltepec, Oaxaca. Diameter growth was measured bimonthly by using dendrometer bands. Six diameter categories, three symmetries categories and three sunlight exposition levels were tested. Moist and relatively dry periods of time were selected during measurements operations, and their influence on tree growth was examined. To determine growth periodicity, the cambium of one tree per diameter category was labeled. Ring width was related with precipitation. S. parahyba grew faster than V. guatemalensis which showed a continuous growth rate. In S. parahyba, the largest diameter categories grew the most (P ≤ 0.05) and no affinity with any radiation condition was found. No differences in growth in diameter categories, symmetries and illuminations crown of V. guatemalensis were found. Both species produced annual rings, completely conspicuous in S. parahyba and slightly delineated in V. guatemalensis. Ring width was highly related with moist periods in S. parahyba (P ≤ 0.01).